Gambaran Sikap dan Dukungan Keluarga dalam Kepatuhan Penerapan Protokol Kesehatan COVID-19 pada Atlet Basket - Salma Sabira; M Sakundarno Adi; Nissa Kusariana; M Arie Wurjanto (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
A sports competition in Indonesia, namely the Indonesian Basketball League (IBL), reported that 10 players had tested positive for COVID-19. Based on the results of the preliminary survey on athletes, ranging its ages from 11-13 years, at basketball club X of Semarang City, it was revealed that 96.9% of the athletes did not use masks during practice's break time on the court's sidelines and 53.1% of athletes never implied social distancing outside the court. This study aims at describing the compliance's implication of the COVID-19 health protocol during the training of basketball athletes at Club X of Semarang City with familial support and attitudes as the parameter. This study used a cross-sectional study design and took the entire study population to be approximately 86 athletes. The research variables consisted of attitudes, family support, and compliance towards the implementation of the COVID-19 health protocol. This study indicated that the proportion of non-compliant athletes (57%) is greater than the proportion of compliant athletes (43%) in implementing the COVID-19 health protocol during the training. Athletes who experienced family support (56,8%) and a positive attitude (53,3%) tended to comply with the covid-19 health protocol during training. It is suggested for the management of basketball club X to conduct socialization related to the use of masks and to maintain the distance during practice's break time on the sidelines for compliance improvement.